Semi-presidentialism sub-types and democratic performance - Elgie, Robert (Oxford : Oxford University Press, 2011)
Robert Elgie examines the relationship between semi-presidentialism and democratic performance. There are over 50 countries with a semi-presidential constitution. The book shows that the president-parliamentary sub-type is more likely to be associated with a poorer democratic performance than its premier-presidential counterpart.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Presidents; Democracy; Cabinet system; Legislative power